Small intestinal stricture complicating superior mesenteric vein thrombosis. A study of three cases. Issue 2 (August 1995) - Eugène, C; Valla, D; Wesenfelder, L; Fingerhut, A; Bergue, A; Merrer, J; Felsenheld, C; Moundji, A; Etienne, J C
Abstract : Mesenteric vein thrombosis associated with intestinal stricture, as a consequence of intestinal ischaemia, has only been mentioned twice in published works. The clinical, biological, and morphological aspects as well as the treatment of this morbid association were studied in three patients. In all, a two stage clinical course (initial acute abdominal pain and fever, followed by chronic intestinal obstruction), corresponding to the sequence thrombosis/stricture, was found. x Ray studies showed a regularly contoured intestinal stricture. Surgical resection was required in all three cases for stricture, associated in one case with mesenteric infarction. Anticoagulation treatment was used to preclude recurrence. Increased clinical awareness could lead to the diagnosis of intestinal stricture secondary to mesenteric vein thrombosis more often and at an earlier stage. Treatment consists of evaluation of predisposing features, intestinal resection when necessary, and anticoagulation therapy, as indicated.